Denial of a right and extraterritoriality: strengthening the fight against tax fraud. (3rd July 2015) - Sutich, Maria Teresa; Centore, Paolo
Abstract : The judgment of the European Court of Justice C-131/13 of 2014, Italmoda, besides confirming the principles already established on the consequences arising from the participation of the taxpayer to a tax fraud on VAT, introduces the principle of the extraterritoriality of the effects of tax fraud in the hands of the traders. The partial fulfillment of the obligations of information, limited to the jurisdiction of origin, as part of a fraudulent plan is no longer sufficient to ensure the rights of the taxpayer in the country of establishment. Cooperation between member states must be understood as not limited to the activities of national administrations because in the case of evasion, avoidance or abuse interaction among different judicial entities is justified through the possibility of reviewing transactions carried out simultaneously to recover unlevied taxation through conduct that can be considered unlawful or contrary to the purposes of the Directive.